The Effect of Working Capital on Profitability (Roa) at PT. Tiga Pilar Sejahtra Food, Tbk Period (2018-2022) Listed on the Indonesian Stock Exchange - Ika Cahyati Nur Amin; Abdul Muttalib; Tenri Syahriani (Agency Journal of Management and Business, 2024)
The aim of this research is a type of quantitative research with the aim of finding out whether working capital has an effect on profitability (ROA) at PT Tiga Pilar Sejahtra Food, Tbk for the period 2018 - 2022. The type of data used in this research is quantitative. Data collection was carried out using financial report collection techniques which were accessed via the website www.idx.co.id. In this research, the data sources used in data collection include secondary data. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) Version 26 application regarding the effect of working capital on profitability (ROA) at PT. Tiga Pilar Sejahtra Food, Tbk for the period (2018 – 2022) which was listed on the Indonesian Stock Exchange which was discussed in the previous chapter, the author draws an important conclusion, namely that working capital has a positive and significant effect on profitability (ROA). This is proven by the results of the t test calculation, namely tcount > ttable (3.648 > 3.18) and the significance value of working capital < 0.05 (0.036 < 0.05) and the correlation test value (R) of 0.903. Working capital must be in line with profitability, because stable and continuously increasing working capital and profitability will invite investors to invest their shares in PT Tiga Pilar Sejahtra Food, Tbk.